Moderating role of Demographics: Personality and Organization Citizenship Behavior among IT sector employees - Ms. Richa Manocha, Dr. Taranjeet Duggal, Dr. Neeti Rana (International Journal of Advanced Science and Technology, 2020)
This research paper is focused towards studying the moderating effect of demographics namely age, gender and designation of the employees on the relation between Personality factors and OCB among IT sector employees. The study is descriptive in nature. Indian IT sector employees (n-504) participated in the survey and filled questionnaires consisting of measures of Personality and OCB. Measurement was done for young & old, male & female and senior & junior employees. Results show that the relationship between Personality factors and OCB is moderated by demographics namely age, gender and designation. The study illustrates that dimensions of personality and OCB will be useful in studying workplace stereotype of age, gender and experience.